Uma abordagem educacional no Colégio Estadual Democrático Bertholdo Cirilo dos Reis sobre conceitos de astronomia básica e tecnologia espacial - Santos, Irineu (2020)
Astronomy is considered one of the oldest sciences, but the development of space technology began in the context of the Cold War, a dispute between the Union of Soviet Socialist Republics (USSR) and the United States of America (USA). The objective of both was to conquer the domains of space. Russia was the pioneer in conquering space, placing the Sputnik 1 satellite and the astronaut, Yuri Gagarin in space. The Americans responded by making radical changes to the school curriculum and creating governing bodies in space technology like NASA (National Aeronautics and Space Administration). The insistence and scientific investment of both countries were fundamental for man to step on lunar soil. Upon conquering space, several human-made objects began to populate the space environment, such as: artificial satellites, probes, space stations, telescopes, etc. There were many benefits of conquering space that return directly or indirectly to society, from the conquest to the present moment, even if they are not perceptible to the understanding of the majority. An example of this is long distance communication services, which have benefited society a lot, with services provided by companies holding patents, technologies and the right to place artificial satellite in space. Despite having completed more than 50 years that the first man went to the Moon, the teaching of Astronomy in Basic Education is not as present as it should be, if its importance in the different segments of society is considered. The debates related to the various space missions, as well as the social contribution of Astronomy, are restricted to academic environments, space research institutes and space agencies. The absence of this debate in the education of elementary and high school students, contributes to the formation of a mass of people alien to this knowledge that influence technologies present in these people's daily lives. For example, mobile telephony, internet, GPS, among others, all these services dependent on satellites (equipment developed from the evolution of space science). Artificial satellites come from space technology and have become allies of communications, climate monitoring, military security, as well as knowing the orbits of NEO (Near-Earth Object), NEA (Near Earth Asteroids) and PHA (Potentially Hazardous Asteroids), in order to help plan the most appropriate mitigation strategies, in order to avoid possible collisions of meteoroids and asteroids with Earth. Society enjoys several benefits from the technologies that are at its disposal, this has led industries to manufacture more and more technological products, such as spaceships, space shuttles, artificial satellites, etc. However, many students and even university students are not convinced that man has gone to the moon. Others do not know the details of this significant episode in scientific history, and are unaware of the facts that preceded the first space trip. This work developed a strategy and possible teaching-learning to Teach Astronomy and Space Technology to Basic Education students. Unveiling other themes and concepts such as Asteroid, Meteorites, Space Debris, Artificial Satellites, Space Maneuvers, Collisions with Earth and their implications for life on the planet. The Physical discipline has a vast content to be addressed in High School, due to its insufficient workload; the teacher is forced to select the most important topics. Most of the time, the subject of Astronomy is not taught and when the teacher tries to introduce more of these contents in his classes, sometimes he does it without due depth. This Dissertation presents a teaching experience in Astronomy held at a public school, Colégio Estadual Democrático Bertholdo Cirilo dos Reis, culminating in a Science and Astronomy Fair. The learning theory that supported this activity was based on the conception of the North American psychologist and pedagogue Jerome S. de Bruner. The Science and Astronomy Fair, was an exhibition of the making of models of some space objects and optical instruments used in Astronomy. The activity had a good repercussion among the school community, was visited by several teachers and students from other classes and contributed to improve the academic performance of the students who participated in the Project. The results of the researches of this scientific work provided bases to elaborate also an educational product, a Paradidático, with the title: "Astronomy for Basic Education". The Paradidático is divided in three parts; First part: basic concepts of Basic Astronomy, Space Technology and small bodies, such as: meteoroid, comets, asteroids and space debris; Second part: some mathematical applications in Astronomy, such as: space maneuvers, escape velocity, etc. Third part: activity suggestions for the teacher to make his classes more dynamic. The educational product and the lived experience are contributions for teachers who have difficulties in including the subjects of Astronomy in their classes.